2011
DOI: 10.3899/jrheum.101054
|View full text |Cite
|
Sign up to set email alerts
|

Thrombovascular Events Affect Quality of Life in Patients with Systemic Lupus Erythematosus

Abstract: The combination of SLE and TE has a more negative influence on reported HRQOL, compared to having SLE or APS alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 12 publications
1
15
0
1
Order By: Relevance
“…24 Only MH appeared to be similarly affected in both APS populations, echoing previous findings. 25,26 Results appeared to suggest that HRQoL was generally poorer for mental domains in PAPS patients compared to SLE 10 had previously reported that having two serious conditions was associated with worse HRQoL compared to having only APS or SLE alone. Present findings indicate that having PAPS alone might be linked to poorer mental HRQoL despite overall better physical HRQoL compared to having SLE alone.…”
Section: Discussionmentioning
confidence: 65%
“…24 Only MH appeared to be similarly affected in both APS populations, echoing previous findings. 25,26 Results appeared to suggest that HRQoL was generally poorer for mental domains in PAPS patients compared to SLE 10 had previously reported that having two serious conditions was associated with worse HRQoL compared to having only APS or SLE alone. Present findings indicate that having PAPS alone might be linked to poorer mental HRQoL despite overall better physical HRQoL compared to having SLE alone.…”
Section: Discussionmentioning
confidence: 65%
“…Thrombotic events appeared to have a particularly profound impact on employment, even after adjustment for potential confounders in the multivariable Cox regressions. Prior studies have demonstrated that thrombotic events are associated with decreased quality of life (20), mortality (21), and irreversible organ damage (22). Although musculoskeletal and neuropsychiatric manifestations were also associated with the risk of work loss in the bivariable analysis, the addition of covariates to the multivariable models reduced their effect slightly.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed the HRQoL using the Medical Outcomes Study Short‐Form 36 (SF‐36), a generic instrument used in chronic diseases including PAPS . This instrument contains eight dimensions and two subscales: mental and physical.…”
Section: Methodsmentioning
confidence: 99%
“…reported that a history of arterial thrombosis was the major factor affecting HRQoL . Other authors found that PAPS patients have significantly worse HRQoL scores in mental domains, but better than systemic lupus erythematosus (SLE) patients in physical domains . Furthermore, PAPS patients self‐reported that main issues related to impaired QoL were pain, fatigue, lack of healthcare professional education and medication .…”
Section: Introductionmentioning
confidence: 99%